Association of Prenatal Alcohol Exposure and Offspring Depression: A Negative Control Analysis of Maternal and Partner Consumption. (21st April 2020) - Easey, Kayleigh E.; Timpson, Nicholas J.; Munafò, Marcus R.
Abstract : Background: Previous research has suggested that intrauterine alcohol exposure is associated with a variety of adverse outcomes in offspring. However, few studies have investigated its association with offspring internalizing disorders in late adolescence. Methods: Using data from the Avon Longitudinal Study of Parents and Children (ALSPAC), we investigated the associations of maternal drinking in pregnancy with offspring depression at age 18 and 24 ( n = 13, 480). We also examined partner drinking as a negative control for intrauterine exposure for comparison. Results: Offspring of mothers that consumed any alcohol at 18 weeks gestation were at increased risk of having a diagnosis of depression (fully adjusted model: OR 1.17, 95% CI 1.02 to 1.34), but there was no clear evidence of association between partners' alcohol consumption at 18 weeks gestation during pregnancy and increased risk of offspring depression (fully adjusted model: OR 0.87, 95% CI 0.74 to 1.01). Postestimation tests found a positive difference between the association of maternal and partner alcohol use on offspring depression, showing a stronger association for maternal compared with partner alcohol use (OR 1.41, CI 1.07 to 1.84). Conclusions: Maternal drinking in pregnancy was associated with increased risk of offspring depression at age 18. Residual confounding may explain this association, but the negative control comparison of paternal drinking provides some evidence that it may be causal, and this warrants further investigation.